Validating the Chinese version of the psoriasis epidemiology screening tool and early arthritis for psoriatic patients questionnaires. Issue 11 (5th June 2021) - Lu, Chao-Fan; Leng, Xiao-Mei; Zeng, Xiao-Feng; Long, Yin; Shi, Yu
Abstract : Supplemental Digital Content is available in the text